Role of Aspirin in Pregnancy with High Gestosis Score and Outcome (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Preeclampsia and eclampsia are the second and third most common causes of maternal morbidity and mortality worldwide. Hypertensive disorders in pregnancy gestosis score (HDP-Gestosis score) was devised in India by Dr. Gorakh Mandrupkar with modifications by a committee is being used for the effective screening and prediction of preeclampsia. High score carries almost 83% sensitivity and 98% specificity for predicting the development of preeclampsia. Acetylsalicylic acid (Aspirin) demonstrates inhibitory effects on Cyclooxygenases (COX) leading to decrease synthesis of prostaglandins and thromboxane-A2 resulting inhibition of both inflammation and platelet aggregation which reduces the risk of developing hypertension and preeclampsia. The purpose of the study to observe the outcome of aspirin use in patients with high gestosis score. Materials and methods: This descriptive observational study in a population 250 pregnant women with high gestosis score (>=3) from January 2021 to December 2022 in the Department of Obstetrics and Gynaecology of Chattagram Maa-OShishu Hospital Medical College. But at the end of the study period only 100 eligible candidates were taken for analysis of results, because 150 cases excluded due to denying to further follow up and termination of pregnancy were done in other centres. After getting an eligible patient through inclusion and exclusion criteria, informed consent was obtained describing the objectives and nature of the study. Demographic details were taken by means of case record form. Details of clinical data, investigation profile including abdominal sonography, biochemical parameters were recorded. Privacy and confidentiality was explained to the patient and maintained. Pregnant mother with high gestosis score were given Tablet Aspirin 75mg / 150mg (According to BMI) daily, during their first Ante-Natal Check-up (ANC) from 12 weeks to 32 weeks. Regular follow up (Minimum 4) was ensured. Data from admitted patient, follow up, termination, mood of delivery, feto maternal outcome up to discharge. Data were analyzed by percentage. Results: Of the 12973 obstetric patients 1396 (10.76%) were presented with hypertensive disorders and among them 100 patients with high Gestosis score were included in our study as they successfully completed the follow up schedule (>4 visit), took regular dosage of Aspirin and termination of pregnancy with postpartum care was taken in our institute. In our study the mean age was found 28.69 years with mean BMI of 23.5 kg/m2. 10.76% of admitted obstetric patients presented with hypertensive disorders of pregnancy. 69% mother e in 20-35 years and 7% under 19 years and 24% more than 35 years. 75% were multipara e 65% had LSCS. 79% were patient e in normal BMI 14% Obese. Risk factor 41% pregnant women gestational hypertension, 39% GDM, 27% hypothyroid and others. 63% women e high gestosis score started Tablet Aspirin within 20 weeks of gestation. 84% women had uneventful outcome e Tablet Aspirin but 11% developed preeclampsia, 5% maternalnearmiss (2 LVF, 2 PPH, 1 PPE). 74% women had term delivery only 20% had preterm termination. 74% baby e good APGER SCORE, LBW were 16% and VLBW were 7%, 2% still birth. Conclusion: HDP-gestosis score is a novel marker to predict the development of preeclampsia with high diagnostic accuracy. HDP-gestosis scoring and Aspirin intake for preeclampsia, have remarkable impacts on maternal and fetal health and wellbeing.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 78-83